Pengendalian Kualitas Produk Sari Buah Markisa Dengan Label “Luxury Seeowrens” Melalui Analisis Kadar Vitamin C, Kalsium Dan Aktivitas Antioksidan Untuk Mitra Markisa Manis Mampang, Pancoran Mas,Kota Depok, Jawa Barat - Hotlina Nainggolan; Dina Melia Oktavilantika; Harits Atika Ariyanta; Dyah Mieta Setyawati (Jurnal Insan Pengabdian Indonesia, 2023)
Community Service Activity Program, Gunadarma University Pharmacy Study Program in collaboration with Gunadarma University LPM, seeks to control the quality of passion fruit juice drink products with the label "Luxury Seeowren" for Mitra Passion Fruit Manis Mampang, Depok City through analysis of nutritional content in the form of vitamin C levels, calcium and antioxidants. The method used in implementing community service is a community development model based on local communities. Change techniques for building community capacity are education, participation, guidance, counseling, research and others. The methods used in vitamin C analysis are titimetry, the calcium test method with ICP-OES, and antioxidant activity measurements carried out using the DPPH method with a UV spectrophotometer. The results of the analysis showed that the calcium content was 9.56 mg/100g, vitamin C 239,335 mg/L, the average antioxidant IC 50 value was 68489.04 mg/L. Based on the results of the nutritional analysis of the passion fruit juice product with the label "Luxury Seeowren" in the form of calcium levels, vitamin C levels and antioxidant activity, it can be concluded that it still does not meet the daily nutritional needs. In the future, it is hoped that we can formulate the right composition for packaged products and can also carry out further tests on product stability and expiration date.